Alternative design of medium rise building (MRB) for low middle income group - Manalang, Ringer T. (College of Architecture, University of the Philippines, Diliman, 1999)
Abstract: This descriptive study is concerned with identifying, describing, and analyzing some of the user's perception of unsatisfied needs in Medium Rise Buildings (MRBs) in Metro Manila. Specifically, the study aimed to find out the users' perception of the MRBs they are presently occupying to identify the legitimate issues and needs that must be addressed in design MRBs taking into consideration the users needs. The data gathering was accomplished-through questionnaire-interview. A total of 50 tenants-respondents had varied complaints regarding several aspects of living in MRBs such as floor area requirements, ventilation, sanitation and beautification as well as security. Upon analyses of the issues and needs that arise, an alternative design of MRB was made. This study showed that a solution to housing problem is possible through an alternative design of housing that is based on the perceived needs of the tenants.